Whole‐Genome Sequencing Reveals SNP ‐Based Genetic Diversity and Population Structure of the Thai Rice Blast Fungus - Apinya Longya; Worrawit Suktrakul; Mantira Suksirt; Siripar Korinsak; Wirulda Pootakham; Nonglak Parinthawong; Ian Lorenzo Quibod; Van Schepler‐Luu; Theerayut Toojinda; Sureeporn Kate‐Ngam; Guo‐Liang Wang; Chatchawan Jantasuriyarat (Plant Pathology, 2025)
ABSTRACT Rice blast, caused by Magnaporthe oryzae , is a devastating disease threatening global rice production. While Southeast Asia is a centre of origin, the pathogen's population dynamics in Thailand are not well understood. We analysed whole‐genome sequences from 191 M. oryzae isolates (60 from Thailand and 131 global) to investigate their genetic diversity, structure and pathogenicity. Phylogenomic analysis revealed that Thai isolates cluster with other Asian populations but exhibit greater within‐population diversity, forming two major genetic clusters. We found that Thai rice isolates from rain‐fed lowland and irrigated rice in the northeast and central regions cluster in World Group 3, while isolates from upland rice in northern Thailand cluster in World Group 1. This revised interpretation provides a more accurate representation of the population structure and highlights previously uncharacterised diversity. To link molecular data with phenotypes, we performed avirulence gene profiling and pathogenicity assays on 31 rice blast resistance near‐isogenic lines. A correlation analysis showed a strong relationship for key gene pairs, including AvrPik and AvrPi9 , highlighting their functional importance. In contrast, the correlation was low for Pii , Pizt and Pib due to the low frequency of their corresponding avirulence genes. The Avr‐Pita interaction displayed a complex, haplotype‐specific correlation. Our findings provide new insights into the genomic and pathogenic variation of M. oryzae in Thailand, establishing a robust link between avirulence gene profiles and observed pathogenicity phenotypes. This work offers a refined foundation for region‐specific resistance breeding and disease management strategies.
Keywords: Plant Pathogens and Fungal Diseases; Mycorrhizal Fungi and Plant Interactions; Yeasts and Rust Fungi Studies